PENGARUH FAKTOR PSIKOLOGIS, KONSEP TRI KAYA PARISUDHA DAN PEMAHAMAN AKUNTANSI TERHADAP PENGELOLAAN KEUANGAN MAHASISWA (STUDI KASUS PADA MAHASISWA PRODI AKUNTANSI UNIVERSITAS MALAHAYATI) - Alansori, Apip; Hakiki, Candra; Kurniawati, Ade (Institut Rahmaniyah Sekayu, 2025)
This research aims to examine the influence of psychological factors, the Tri Kaya Parisudha concept and understanding of accounting on student financial management Student. The data collection method in this research is primary data, namely questionnaires and observations of the research object. The data analysis technique used in this research is Multiple Linear Regression Analysis. The type of research used is quantitative descriptive. The sampling method used was random sampling with a total sample of 55 who were students of the accounting study program at Mahalayati University class of 2021-2022. The independent variables used are psychological factors, the tri kaya parisudha concept and understanding of accounting. The dependent variable used is student financial management. The data used in this research is primary data. The data analysis method used is Multiple Linear Regression. The results of this research show that the Psychological Factor variable has an influence on student financial management, the Tri Kaya Parisudha concept has no influence on student financial management, while understanding accounting has no influence on the financial management of Malahayati University Accounting Study Program students.